Optimal. Leaf size=27 \[ \frac {1}{16} \left (e^5-e^{\frac {3 x}{4}+e^{-x^2} x}\right ) \]
________________________________________________________________________________________
Rubi [F] time = 0.59, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {1}{64} e^{-x^2+\frac {1}{4} e^{-x^2} \left (4 x+3 e^{x^2} x\right )} \left (-4-3 e^{x^2}+8 x^2\right ) \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{64} \int e^{-x^2+\frac {1}{4} e^{-x^2} \left (4 x+3 e^{x^2} x\right )} \left (-4-3 e^{x^2}+8 x^2\right ) \, dx\\ &=\frac {1}{64} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} \left (-4-3 e^{x^2}+8 x^2\right ) \, dx\\ &=\frac {1}{64} \int \left (-4 e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x}-3 e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x+x^2}+8 e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} x^2\right ) \, dx\\ &=-\left (\frac {3}{64} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x+x^2} \, dx\right )-\frac {1}{16} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} \, dx+\frac {1}{8} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} x^2 \, dx\\ &=-\left (\frac {3}{64} \int e^{\frac {3 x}{4}+e^{-x^2} x} \, dx\right )-\frac {1}{16} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} \, dx+\frac {1}{8} \int e^{\frac {1}{4} \left (3+4 e^{-x^2}-4 x\right ) x} x^2 \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.25, size = 21, normalized size = 0.78 \begin {gather*} -\frac {1}{16} e^{\frac {3 x}{4}+e^{-x^2} x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.95, size = 33, normalized size = 1.22 \begin {gather*} -\frac {1}{16} \, e^{\left (x^{2} - \frac {1}{4} \, {\left ({\left (4 \, x^{2} - 3 \, x\right )} e^{\left (x^{2}\right )} - 4 \, x\right )} e^{\left (-x^{2}\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.20, size = 15, normalized size = 0.56 \begin {gather*} -\frac {1}{16} \, e^{\left (x e^{\left (-x^{2}\right )} + \frac {3}{4} \, x\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.04, size = 21, normalized size = 0.78
method | result | size |
risch | \(-\frac {{\mathrm e}^{\frac {x \left (3 \,{\mathrm e}^{x^{2}}+4\right ) {\mathrm e}^{-x^{2}}}{4}}}{16}\) | \(21\) |
norman | \(-\frac {{\mathrm e}^{\frac {\left (3 \,{\mathrm e}^{x^{2}} x +4 x \right ) {\mathrm e}^{-x^{2}}}{4}}}{16}\) | \(23\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.40, size = 15, normalized size = 0.56 \begin {gather*} -\frac {1}{16} \, e^{\left (x e^{\left (-x^{2}\right )} + \frac {3}{4} \, x\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.19, size = 15, normalized size = 0.56 \begin {gather*} -\frac {{\mathrm {e}}^{\frac {3\,x}{4}}\,{\mathrm {e}}^{x\,{\mathrm {e}}^{-x^2}}}{16} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.37, size = 20, normalized size = 0.74 \begin {gather*} - \frac {e^{\left (\frac {3 x e^{x^{2}}}{4} + x\right ) e^{- x^{2}}}}{16} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________